Isolation of the gut probiotics and application in early stages larviculture of blue swimming crab, Portunus pelagicus (Linnaeus, 1758) - Dad Talpur, Mir Allah (Terengganu: Universiti Malaysia Terengganu, 2014)
Survival problems of Portunus pelagicus larvae rearing are encountered at early stages owing to pathogenic microbes. In rearing system pathogens enter either shed by adult female in spawning tanks or from live feed fed to larvae. To determine the pathogen prevalence in the gut of female P. pelagicus crab the study was conducted.